2021
DOI: 10.1136/bmjopen-2020-046667
|View full text |Cite
|
Sign up to set email alerts
|

Piloting gender-oriented colorectal cancer screening with a faecal immunochemical test: population-based registry study from Finland

Abstract: ObjectiveTo assess the feasibility and evaluate the performance of a relaunched colorectal cancer (CRC) screening programme with different cut-offs for men and women.DesignPopulation-based registry study.SettingNine municipalities in Finland which started CRC screening with faecal immunochemical test (FIT) in April 2019 with cut-off levels 70 µg Hg/g faeces for men and 25 µg Hg/g faeces for women.ParticipantsMen (n=13 059) and women (n=14 669) aged 60–66 years invited to screening during the first programme ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
0
20
1
1
Order By: Relevance
“… 2 In addition, a recent study from Finland showed that using > 25 μg Hb/g faeces for women and > 70 μg Hg/g faeces for men gave similar CRC detection rates in both genders (0.16% for women and 0.18% for men) and similar PPV for CRC (6.4% for women and 6.6% for men). 25 However, in this Finnish study, the positivities in women and men using these thresholds were 2.6% and 2.4%, respectively. These positivities are considerably lower than those currently observed at similar thresholds in Scotland, perhaps due to demographic factors such as lifestyle, and also because f-Hb concentrations found are highly dependent on the FIT system employed, 26 so the results from Finland are not necessarily transferable over geography.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“… 2 In addition, a recent study from Finland showed that using > 25 μg Hb/g faeces for women and > 70 μg Hg/g faeces for men gave similar CRC detection rates in both genders (0.16% for women and 0.18% for men) and similar PPV for CRC (6.4% for women and 6.6% for men). 25 However, in this Finnish study, the positivities in women and men using these thresholds were 2.6% and 2.4%, respectively. These positivities are considerably lower than those currently observed at similar thresholds in Scotland, perhaps due to demographic factors such as lifestyle, and also because f-Hb concentrations found are highly dependent on the FIT system employed, 26 so the results from Finland are not necessarily transferable over geography.…”
Section: Discussioncontrasting
confidence: 53%
“… 11 , 12 Thus, the issue of whether or not partitioned f-Hb thresholds should be used for women and men can only be resolved by prospective, observational studies. The distributions of f-Hb concentrations in men and women with CRC, the newer data from Scandinavia, 25 , 28 and other evidence on screening outcomes, as detailed above, indicate that lowering the f-Hb concentration threshold in women would increase the chances of detecting CRC in those participating in screening. However, there are areas of significant uncertainty and these include the extent to which CRC detection rates in women and men would converge, the effect on the PPV and the consequent harms of any increase in the false positive rate, the effect on interval cancer rates in women and the cost-effectiveness of this strategy.…”
Section: Discussionmentioning
confidence: 92%
“…Unexpectedly, we found no statistically significant difference in CRC incidence between men and women. Numerous studies have suggested that the FIT is more sensitive in men than in women, as women more often have right-sided cancer, which tends to bleed less 16 17 18 . Therefore, we would have expected the number of cancers in the FIT-negative group to be higher in women than in men.…”
Section: Discussionmentioning
confidence: 99%
“…How to further stratify the target screening population becomes an important issue. Using age- and gender-specific FIT cutoffs or applying a risk scoring system that accommodates common risk factors may become feasible solutions ( Chen et al, 2018 ; Sarkeala et al, 2021 ; Chiu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%